Problem with the superstring action of Deriglazov and Galajinsky - Berkovits, Nathan [UNESP] (Amer Physical Soc, 1999)
Deriglazov and Galajinsky have recently proposed a new covariant action for the Green-Schwarz superstring which can be constructed in any spacetime dimension. In this Comment, I show that their action contains extra on-shell degrees of freedom as compared with the standard action and is therefore inequivalent. ©1999 The American Physical Society.